Optimalisasi Moderasi Beragama Penyuluh dan Guru Melalui Forum Ruang Perjumpaan - Muhammad Ihyakulumudin (JURNAL ILMIAH GEMA PERENCANA, 2024)
The main actors of the Ministry of Religious Affairs that should be prioritized for strengthening religious moderation are instructors and teachers. Measuring the implementation of the religious moderation promotion training program for counselors and teachers resulted in several main things that need to be evaluated. Among the problems found in implementing this training are: First, moderation training has not been able to reach a wide range of participants due to limited quotas and priorities for civil servant employees. Second, the results of measuring the attitudes and understanding of moderation of civil servants and non-civil servants at the Ministry of Religious Affairs are not much different. Third, the results of measuring attitudes and understanding of religious moderation of teachers are lower than those of counselors. Fourth, the main duties and functions of teachers and counselors are different, but both are required to master the same religious moderation. In explaining these matters, the author uses the bibliographic method. This article attempts to formulate several policy recommendations that can be used by the Ministry of Religious Affairs regarding programs to strengthen religious moderation. The conclusion of this article is that a review of standard operational procedures for implementing religious moderation training is needed and regulations from the Directorate General of Islamic Education are needed that encourage active meeting spaces for teachers under the Ministry of Religious Affairs.